Information modelling of dynamic impacts on a unique building of a multifunctional complex of parametric architecture - E. K. Agahanov; M. K. Agahanov; E. V. Trufanova (Vestnik MGSU)
Introduction. The study of corrugated surface shaping with subsequent shape selection for creating volumetric planning solutions for the building frame was performed. Surface shaping was performed in the SAPFIR software package. The corrugated surface and cyclic surface were combined to create the architectural appearance of a unique building of a multifunctional complex. The calculation of the analytical model of the frame of a unique multifunctional complex of parametric architecture was performed using the finite element method and the selection of optimal design solutions was performed. Additionally, the effect of adding outrigger floors to the finite element model at different levels of the building frame was studied.Materials and methods. The corrugated surface was formed in the SAPFIR software package. The finite element model was obtained by exporting the analytical model to the Lira-SAP. software package. To confirm the correctness of the adopted design solutions for the building frame, a study was conducted on the stress-strain state of the structures, the frequency and shape of natural vibrations. Four options for the location of outrigger systems were proposed, and the influence of outrigger floors on the dynamic response of the building frame was studied.Results. As a result of the calculations, the values of horizontal displacements of the building frame were obtained, which do not exceed the standard values. The change in design solutions allowed to make the first and second forms of oscillations translational, the third — torsional. The obtained nature of the dynamic response shows the efficiency of the adopted design solutions of the unique building frame. The numerical experiment allowed to achieve a reduction in horizontal displacements by 25 %, which increases the overall stability and spatial rigidity of the building frame.Conclusions. As a result of the study, a form of a unique building of parametric architecture was obtained. A study of the influence of outrigger systems on the dynamic characteristics of the building frame was carried out. Based on the research results, the frame of a unique building of a multifunctional complex meeting the requirements of reliability and cost-effectiveness is developed.